Neurocirugía ablativa multitarget para tratamiento de trastorno neuroagresivo recidivante - García Muñoz, Luis; Ujhelly, Jose Ignacio; Beltrán, Jesus Q.; Fazzito, Maria Lucia; Jiménez-Ponce, Fiacro (Revista Argentina de Neurocirugía, 2022)
Neuroaggressive disorder (NAD) is one of the main requests for psychiatric neurosurgery since it is common to observe treatment resistance. Two types of ablative surgeries have been proposed. One of them is more extensive, which involves performing three extended lesions bilaterally within the anterior arm of the internal capsule and two lesions in the supracallosal cingulate cortex . Another less extensive one, which consists of unilaterally lesion of the lateral and central nucleus of the amygdala and the posteromedial hypothalamus. This article presents two cases of patients with refractory NAD who had previously undergone surgery and required a new psychiatric neurosurgery, to achieve control or reduction of the aggressiveness exhibited.